Optimizing Civil Construction Litigation In Indonesia: A Comprehensive Framework For Efficiency, Expertise, And Equity In Dispute Resolution - Azizan, Akmal; Sophia, Sally; Zahra, Salma; Perai, Nurajam (Jurnal Hukum dan Peradilan, 2024)
Delays, excessive expenses, and a decline in public confidence come from the specialized nature of civil construction litigation in Indonesia. Several efforts have been made to improve civil construction litigation in Indonesia, such as introducing procedural reforms to expedite case processing times, increasing access to mediation and alternative dispute resolution (ADR), and the occasional involvement of technical experts to assist judges in understanding complex construction issues.Â  Â  Unresolved problems continue despite current attempts; a complete system redesign is required. This paper attempts to fill such knowledge gaps and provide fresh approaches to civil construction litigation in Indonesia. This study provides a comprehensive strategy to improve litigation effectiveness, efficiency, and professionalism by incorporating worldwide best practices and offering practical solutions. The research takes a methodical look at effective models in the UK, Germany, France, and Japan. It identifies critical issues in the Indonesian setting and develops specialized procedural tools like "Case Management Information Tables" and "Case Management Plan Tables." A long-term vision for the legal framework is also discussed, along with strategic approaches to expert evidence, creating a qualification and assessment system, the participation of active-standing technical advisors, and more. The study produces a versatile and all-encompassing structure for civil construction litigation in Indonesia. The research fills a need in the literature by providing valuable resources and fresh ideas for improving efficiency in legal procedures, bolstering the credibility of expert testimony, establishing stringent qualifying criteria, and encouraging long-term flexibility. The public's faith and confidence in the Indonesian legal system are bolstered due to these contributions, which increase the process's efficiency and justice.